konstruksi kritik sosial pada lagu "pasar ini telah musnah" karya Jemmie Delvian - kamal Kamal; Reza Aprianti; sepriadi saputra (Jurnal Prodi Ilmu Komunikasi, 2022)
This study contains the analysis of the lyrics of the song “Pasar Ini Has Disnah” which was popularized by Tropical Forests, analyzed using a qualitative method, with a technical approach to Ferdinand De Sausure's semiotic study seen from the signifier and the signified. Data collection techniques are observation, documentation, interviews, literature searches and online. In this study the researchers took 5 stanzas of the song. The song contains a very deep message that the songwriter wants to convey. The lyrics of the song Pasar Ini Has Musnah contain the meaning of criticism, where the songwriter wants to express his deep concern and show an empathy for a condition that is being felt over a problem that exists in Pasar Cinde. In addition, the songwriter also invites the public or listeners to be more open-minded and can be more concerned with the history that exists in the motherland. Music can act as a medium to convey an aspiration, to carry out the function of communication, musicians can see reality and issue social criticisms that are deemed necessary through the songs they compose such as what Jemmie Delvian did in the song “this market has been destroyed”.